Effect of Quality of Irrigation Water on Dry Matter Production, and on Calcium, Magnesium and Phosphorus Content of Wheat, Barley and Pea - Khan, M Usman; Saxena, S N (Annals of Arid Zone, 2016)
The effect of variation in conductivity, SAR values and.boron content of applied irrigation water was evaluated forwheat, barley and pea. In aU the three crops increasing levelsof conductivity, SAR and boron suppressed the dry matterproduction. Calcium absorption was increased in all the threecrops with an increase in conductivity. Magnesium absorptionalso increased in wheat and pea but an antagonistic trend wasrecorded in case of barley. Phosphorus content of pea andwheat increased with increase in conductivity,SAR and boronlevels. Increasing SAR values of irrigation water resulted indecreased calcium and magnesium absorption in wheat andbarley but reverse was true in case of pea. Increasing levelsof boron in irrigation water suppressed calcium absorption inwheat and pea but increased the same in barley. A reversetrend was observed with respect to magnesium. All first orderinteractions have produced significant changes in plants.